Clinical Variability After Partial External Biliary Diversion in Familial Intrahepatic Cholestasis 1 Deficiency. Issue 3 (March 2017) - Squires, James E.; Celik, Neslihan; Morris, Amy; Soltys, Kyle; Mazariegos, George; Shneider, Benjamin; Squires, Robert H.
ABSTRACT: Objectives: Familial intrahepatic cholestasis 1 (FIC1) ** deficiency is caused by a mutation in the ATP8B1 gene. Partial external biliary diversion (PEBD) is pursued to improve pruritus and arrest disease progression. Our aim is to describe clinical variability after PEBD in FIC1 disease. Methods: We performed a single-center, retrospective review of genetically confirmed FIC1 deficient patients who received PEBD. Clinical outcomes after PEBD were cholestasis, pruritus, fat-soluble vitamin supplementation, growth, and markers of disease progression that included splenomegaly and aspartate aminotransferase-to-platelet ratio index. Results: Eight patients with FIC1 disease and PEBD were included. Mean follow-up was 32 months (range 15–65 months). After PEBD, total bilirubin was <2 mg/dL in all patients at 8 months after surgery, but 7 of 8 subsequently experienced a total of 15 recurrent cholestatic events. Subjective assessments of pruritus demonstrated improvement, but itching exacerbation occurred during cholestatic episodes. High-dose fat-soluble vitamin supplementation persisted, with increases needed during cholestatic episodes. Weight z scores improved (−3.4 to −1.65, P  < 0.01). Splenomegaly did not worsen or develop and 1 patient developed an aminotransferase-to-platelet ratio index score of >0.7 suggesting development of fibrosis 24 months after PEBD. Conclusions: Clinical variability is evident among genetically defined FIC1 deficient patients after PEBD, even among those with identical mutations. Recurrent, self-limited episodes of cholestasis and pruritus are reminiscent of the benign recurrent intrahepatic cholestasis phenotype. Despite diversion of bile from the intestinal lumen, weight gain improved while fat-soluble vitamin requirements persisted. Significant progression of liver disease was not evident during follow-up. Abstract : Supplemental Digital Content is available in the text